Kesalahan Penggunaan Konjungsi pada Khotbah Berbahasa Karo - Yesita Primsa Br Ginting; Dairi Sapta Rindu Simanjuntak; Indah Lestari Sinulingga; Putri Sion Dameria Silaen (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
In practice, conjunctions are often found in language. Conjunctions are task words that function to connect linguistic units such as words with words, clauses with clauses, or sentences with sentences in a syntactic relationship. This research discusses the use of conjunctions in Karo language sermons delivered at various traditional and religious events. In making this journal, the benefit is to examine errors in the use of conjunctions in Karo language sermons with a focus on analytical and linguistic syntax. The research method used is descriptive qualitative, the research investigates the pattern of syntactic errors in the use of conjunctions that occur in sermons at the GBKP Ruggun Belawan Church. The research results reveal various typologies of conjunction errors that significantly influence the quality of communication and cohesion of religious discourse.